AHP-MOORA framework for longitudinal evaluation of Pharm.D program learning outcomes: a tool for Saudi pharmacy programs accreditation and curriculum enhancement - Alshahrani, Sultan M. (Frontiers in Medicine, 2025)
IntroductionAs pharmacy education in Saudi Arabia progresses in accordance with Saudi Vision 2030 and international competency-based standards, the necessity for systematic evaluation of Program Learning Outcomes (PLOs) has become essential. This study aimed to establish a scalable framework for evaluating PLOs’ achievement under the National Commission for Academic Accreditation and Assessment (NCAAA) criteria.MethodsA mixed-methods methodology was utilized in a public pharmacy institution in Saudi Arabia. Eight PLOs derived from the Pharm.D program framework were assessed utilizing stakeholder feedback and national quality standards. The analytical hierarchy process (AHP) was employed to prioritize outcomes, while the Multi-Objective Optimization by Ratio Analysis (MOORA) technique was utilized to evaluate performance over five graduating cohorts (2018–2022). Data sources comprised alumni employment data, postgraduate enrollment, and professional practice positions. A program based on Microsoft Access was created for data administration and visualization.ResultsPLO2 (clinical application) and PLO5 (ethics and professionalism) earned the greatest AHP weights, measuring 0.28 and 0.19, respectively. Composite MOORA scores exhibited optimal performance in 2020 (0.883) and declined to 0.792 in 2022. The decline in 2022 may be attributed to reduced clinical training opportunities and delayed workforce absorption following COVID-19-related disruptions, as documented in comparable educational settings. The technology facilitated long-term trend analysis and cohort-specific reporting.ConclusionThe holistic monitoring tool established a durable framework for evaluating PLOs attainment by national accreditation standards. It facilitated evidence-based enhancements to the curriculum and enhanced institutional quality assurance. The widespread application of this strategy in pharmacy colleges, including digital integration and external benchmarking, can increase accreditation preparedness and facilitate ongoing educational enhancement.